Kepatuhan Personal Hygiene Penjamah Makanan Pada Masa Pandemi Covid-19 - Aprilia, Wevri; Pawenang, Eram Tunggul (Indonesian Journal of Public Health and Nutrition, 2023)
Background: Covid-19 is an infectious disease caused by SARS-CoV-2 which was discovered in Wuhan, China in 2019. Food handlers must meet personal hygiene requirements (Kepmenkes No. 1098/Menkes/SK/VIII/2003). The purpose of this study was to determine the factors that influence the personal hygiene compliance of food handlers during the Covid-19 pandemic. Methods: Analytical descriptive research with cross sectional design. A sample of 80 handlers. The dependent variable: personal hygiene compliance, and the independent variables: age, gender, education level, length of work, knowledge, attitudes, behavior, hand washing facilities, monitoring market officers, and market information media. The instruments used were questionnaires and observation sheets. The sampling technique is proportional random sampling. Results: the results of the Chi-Square Test analysis showed age (p=0.109), gender (p=1,000), years of work (p=1,000), education level (p=0.017), knowledge (p=0.159), attitudes (p = 0.014), action (p = 0.004), hand washing facilities (p = 1,000), monitoring of market officers (p = 0.106), market information media (p = 1,000). Conclusion: age, gender, length of work, knowledge, facilities hand washing, monitoring market officers and market information media are not related to personal hygiene compliance. The level of education, attitudes and actions have a relationship with personal hygiene compliance.